О СООТНОШЕНИИ СКОРОСТЕЙ СОВРЕМЕННОЙ ДЕНУДАЦИИ И ТЕКТОНИЧЕСКИХ ПОДНЯТИЙ ЭПИГЕОСИНКЛИНАЛЬНЫХ ГОР ЕВРАЗИИ - Мамина Л.Р. (My University, 2005)
Recent mechanical denudation rate in Alps, Carpathians, West and East Caucasus, and Himalayas was estimated by the sediment discharge data. The values obtained were compared with tectonic uplift velocities. Everywhere within the axial zone of the mountains the tectonic uplift predominates denudation in ratio 1.8:1 - 6.4:1. This indicates the continuous upward evolution of mountains. Recent rates of mountains uplift are higher than average rates for the whole neotectonic stage.
Keywords: 551.432(-924/-925)